PENGARUH PEMBERIAN SUSU KEDELAI (GLYCINE MAX L. MERR.) TERHADAP GEJALA MENOPAUSE PADA IBU - IBU PENGAJIAN AISYIYAH - RAHMAH EVELIN LUBIS; ROBITAH ASFUR (LP2MTBM MAKARIOZ, 2020)
Menopause is defined as a permanent stop of menstruation due to the loss of ovarian follicular activity due to agingmanifested into aminorea 12 months in a row. Menopause is characterized by a decrease in estrogen levels that causesmany physical and emotional changes that cause many symptoms. Menopausal symptoms can be reduced by consumingsoy milk containing phytoestrogen isoflavones. This study uses a type of one group pre test and post test research design.The sample consisted of 23 women who consumed 250 ml of soy milk for 12 weeks. Menopause Rating Scale (MRS)questionnaires were given to menopausal women before and after consuming soy milk. The results are analyzed usingSPSS. After 12 weeks of consuming soy milk, there was a significant influence (p=0.004) of soy milk administration on theseverity of menopausal symptoms in Aisyid study mothers especially somatic and psychological symptoms.